Characterization of Intsia spp. from Indonesia using microsatellite markers - Purnamila Sulistyawati; Sapto Indrioko; Widiyatno; AYPBC Widyatmoko (Forest Science and Technology)
Microsatellite DNA markers are known to have a high level of genetic diversity and can be used for various purposes. These include population genetic analysis, gene flow assessment, pollen distribution, parent analysis, and accurate distinction between types and varieties. Despite the potential application of microsatellite markers, their development process often requires high costs, energy, and time. To overcome the limitations, several studies have proposed the use of cross-species amplification, which has proven to be a cost and time-efficient method for obtaining species-specific DNA markers. Therefore, this study aimed to identify three species of Merbau in Indonesia, namely Intsia bijuga, I. palembanica, and I. acuminata using cross-species amplification. The three species are known to exhibit similarities in all taxonomical characteristics except for minor differences in the number of leaf pairs per twig and the tip shape of the leaflets. These species also have different levels of economic value and conservation status due to variations in the type of wood produced. Several studies have shown that identification errors can affect the economic value of their wood and logging mistakes can lead to a decrease in the genetic diversity. To address the concerns, Intsia bijuga and I. acuminata from Indonesia were selected as test samples for the cross-amplification of microsatellite markers created for I. palembanica. Due to their taxonomical similarities, the diagnostic characteristics of each Intsia species were assessed based on microsatellite markers. Leaf samples were obtained from three species of Intsia that had been verified and identified based on morphological characteristics by taxonomists from the Bogor Botanical Garden Indonesia. In addition, a total of 10 polymorphic I. palembanica microsatellite markers from the previous literature were used in this study. The results showed that the cross-species amplification of microsatellite locus was successful in all markers. Certain alleles were also observed to be shared by the three species of Intsia, while some were specific to a particular species. These specific alleles could also serve as a diagnostics characteristic for Intsia spp. In addition, a set of polymorphic microsatellites showing a successful transfer across species of Intsia could serve as a valuable tool for comparative studies among related taxa species and breeding and conservation programs.